solve for in y of the other variables
You are given the following equation: y + u = x <==> x = y + u
Looking at the equation, we see that it is solved for x in terms of the other variables, y and u, since it basically states that x is equal to the sum of y and u.
To solve this equation for y in terms of the other variables, x and u, we need to isolate the y variable to one side of the equation by moving all other variables to the other side of the equation.
y + u = x to solve for y, subtract u from both sides of the equation
y + u - u = x - u
y + 0 = x - u
y = x - u